2007
DOI: 10.1016/j.phytochem.2006.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Ferulsinaic acid, a sesquiterpene coumarin with a rare carbon skeleton from Ferula species

Abstract: Fractionation of methylene chloride extracts of the resin of Ferula vesceritensis and F. sinaica afforded three sesquiterpene coumarins and a glucose derivative. One of them was a sesquiterpene with a rare carbon skeleton. The structures of these compounds were determined by extensive NMR studies, including DEPT, COSY, NOE, HMQC, and HMBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The species Ferula asafoetida has been reported to exhibit anti-carcinogenic properties and to afford protection against freeradical-mediated diseases (Saleem, Alam, & Sultana, 2001) and exhibited anti-leishmanial activity against promastigotes (Iranshahi et al, 2007). Previous phytochemical studies of plants from this genus revealed that the main constituents are sesquiterpenes and sesquiterpene coumarins (reviewed in Ahmed et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The species Ferula asafoetida has been reported to exhibit anti-carcinogenic properties and to afford protection against freeradical-mediated diseases (Saleem, Alam, & Sultana, 2001) and exhibited anti-leishmanial activity against promastigotes (Iranshahi et al, 2007). Previous phytochemical studies of plants from this genus revealed that the main constituents are sesquiterpenes and sesquiterpene coumarins (reviewed in Ahmed et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In our recent communication, we reported the isolation and structure elucidation of two new sesquiterpene coumarins (Ahmed et al, 2007;Lahouel et al, 2007) from a methylene chloride extract of F. vesceritensis. It is evident from the literature and previous investigations that the genus Ferula possesses high biological activities (Ahmed et al, 2007), which prompts us to study the anti-cancer activity for the major isolated compound, lapiferin, from F. vesceritensis with different extraction methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mogoltacin (47) was described to significantly enhanced the cytotoxicity of vincristine (by 32.8%) towards human transitional cell carcinoma without causing any toxic effects on the cells (Rassouli et al 2009). The resins of F. vesceritensis and F. sinaica afforded many sesquiterpene coumarins including a compound with rare carbon skeletonferulsinaic acid (51) (Ahmed et al 2007). Ferulsinaic acid (51) …”
Section: Sesquiterpene Umbelliferyl (7-hydroxycoumarin) Ethersmentioning
confidence: 99%
“…Accordingly, plants producing sesquiterpene coumarins may express such squalene epoxidaselike enzymes for the epoxidation of 7-O farnesylated coumarins and the generation of a carbocation analogous to the protosteryl or dammarenyl cation in triterpene biosynthesis (Phillips et al 2006). Following this assumption, biogenetic patterns have been outlined for several natural sesquiterpene coumarins (Appendino et al 1994;Gohar and El-Bassuony 2007;Ahmed et al 2007;Kojima et al 2000;Isaka et al 2001, Nagatsu et al 2002Motai and Kitanaka 2004). Nevertheless, the evidence for these biosynthetic steps was primarily inferred from related terpene pathways and needs further experimental support in case of the sesquiterpene coumarins.…”
Section: Farnesyl Diphosphatementioning
confidence: 99%